Prevalence and extent of infarct and microvascular obstruction following different reperfusion therapies in ST-elevation myocardial infarction - Khan, Jamal N (BioMed Central, 2014)
BACKGROUND: Microvascular obstruction (MVO) describes suboptimal tissue perfusion despite restoration of infarct-related artery flow. There are scarce data on Infarct Size (IS) and MVO in relation to the mode and timing of reperfusion. We sought to characterise the prevalence and extent of microvascular injury and IS using Cardiovascular magnetic resonance (CMR), in relation to the mode of reperfusion following acute ST-Elevation Myocardial Infarction (STEMI). METHODS: CMR infarct characteristics were measured in 94 STEMI patients (age 61.0 ± 13.1 years) at 1.5 T. Seventy-three received reperfusion therapy: primary percutaneous coronary-intervention (PPCI, n = 47); thrombolysis (n = 12); rescue PCI (R-PCI, n = 8), late PCI (n = 6). Twenty-one patients presented late (>12 hours) and did not receive reperfusion therapy. RESULTS: IS was smaller in PPCI (19.8 ± 13.2% of LV mass) and thrombolysis (15.2 ± 10.1%) groups compared to patients in the late PCI (40.0 ± 15.6%) and R-PCI (34.2 ± 18.9%) groups, p <0.001. The prevalence of MVO was similar across all groups and was seen at least as frequently in the non-reperfused group (15/21, [76%] v 33/59, [56%], p = 0.21) and to a similar magnitude (1.3 (0.0-2.8) v 0.4 [0.0-2.9]% LV mass, p = 0.36) compared to patients receiving early reperfusion therapy. In the 73 reperfused patients, time to reperfusion, ischaemia area at risk and TIMI grade post-PCI were the strongest independent predictors of IS and MVO. CONCLUSIONS: In patients with acute STEMI, CMR-measured MVO is not exclusive to reperfusion therapy and is primarily related to ischaemic time. This finding has important implications for clinical trials that use CMR to assess the efficacy of therapies to reduce reperfusion injury in STEMI.